Investigating peer influence on collaborative group members' motivation through the lens of socially shared regulation of learning - Järvenoja, Hanna; Törmänen, Tiina; Lehtoaho, Emma; Turunen, Marjo; Suoraniemi, Jasmiina; Edwards, Justin (British journal of educational psychology, 2025)
Background Social context and peers significantly impact students' motivation, especially in collaborative learning settings. However, there is limited evidence on how students strategically influence each other's motivation through socially shared regulation of learning (SSRL). Aims This study examined secondary school students' SSRL during collaborative learning, focusing on how groups regulate motivation and how these regulation processes influence individual situational motivation through peer interactions. Sample The participants were 95 secondary school students (13–16 years) performing a collaborative science task in 31 groups. Methods Collaborative learning was videotaped to capture motivation regulation from social interactions. Four times during the task, individual perceptions of peer influence on motivation and motivation regulation were collected with situational self‐reports, and individual stimulated‐recall interviews were conducted after the task. Results The results showed that motivation regulation is embedded within broader SSRL processes. When motivation regulation coincided more likely with cognitive regulation, students perceived significantly higher peer influence on motivation. In interviews, students highlighted cognitive and social aspects of SSRL as crucial for their situational motivation but did not hardly recognize any direct motivation regulation strategies. Conclusions This study contributes to the methodological advancements for studying motivation as situation‐ and context‐specific, emphasizing the use of different data channels to capture the dynamic interplay between the individual‐ and group‐level aspects throughout the learning process. For educational practice, this study supports the claim that peer interactions, particularly in collaborative learning, play a crucial role in individual students' motivation.